The Irish economy in transition successes, problems, and prospects - Munley, Vincent; Thornton, Robert J. (Robert James), 1943-; Aronson, J. Richard (Jay Richard), 1937- (Oxford ; Boston : JAI, 2002)
The transformation of Ireland from one of the poorer countries in Western Europe to one of the best performing is one of the most remarkable economic success stories in recent times. The ten papers in this collection were presented at a conference at Lehigh University in March 2001. Written from a broad interdisciplinary perspective, the papers collectively discuss the recent evolution of the Irish economy and the factors responsible. They also analyze the problems that rapid growth has generated and the consequent domestic policy challenges in such areas as infrastructure, the environment, education, and social welfare.
The Irish economy in transition / Vincent G. Munley, Robert J. Thornton -- Fiscal policy and the public finances : creative approaches to pension funding / John McHale -- Privatization of electricity and telecommunications in Ireland / Moore McDowell -- Has Ireland outgrown its clothes? Infrastructural and environmental constraints in Ireland / John Fitz Gerald -- Ireland in the 1990s : the problem of unbalanced regional development / Michael J. Keane -- Ireland's social safety net / Eithne Fitzgerald -- The celtic tiger : a view from the trenches of academia / Michael P. Mortell -- Foreign direct investment : the case of the electronics and pharmaceuticals industries / Joe Durkan -- The Irish economy : recent experience and prospects / Mark Cassidy -- Nurturing indigenous entrepreneurship in Ireland : the case of the it software sector / Connell Fanning, Ciaran Murphy -- Monetary and fiscal policy in EMU / Rodney Thom.
Papers presented at a conference at Lehigh University, March 2001.
Description based on print version record.
Keywords: Business & Economics -- Economic Conditions; Social Science -- General; Macroeconomics; Ireland; Ireland -- Economic conditions -- 1949 -- Congresses; Ireland -- Economic policy -- Congresses